2015
DOI: 10.1021/acs.analchem.5b01192
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of α-1 Antitrypsin in Serum Samples using Surface Plasmon Resonance with a New Aptamer–Antibody Sandwich Assay

Abstract: The challenges associated with performing surface plasmon resonance (SPR) based measurements in serum and other biofluids have continued to limit the applicability of this valuable sensing technology for sensitive bioaffinity measurements of proteins in clinically relevant samples. In this paper, a new sandwich assay is introduced for the quantitative SPR analysis of α-1 antitrypsin (AAT), which is a recognized biomarker for Alzheimer's disease. Detection was performed via the specific adsorption of AAT onto a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
(83 reference statements)
2
27
0
Order By: Relevance
“…Thus, the reason for the unreliable results obtained with kit #1 and #2 is currently unknown. It was recently reported that kit #1 yielded a two-fold difference as compared to an SPRbased assay [25]. This inconsistency could be alleviated by using the protein standard used in their SPR experiments (his-tagged ra1AT expressed in NS0 cells) instead of the pla1AT standard included in the kit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reason for the unreliable results obtained with kit #1 and #2 is currently unknown. It was recently reported that kit #1 yielded a two-fold difference as compared to an SPRbased assay [25]. This inconsistency could be alleviated by using the protein standard used in their SPR experiments (his-tagged ra1AT expressed in NS0 cells) instead of the pla1AT standard included in the kit.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the better control over the probe molecule surface attachment, packing densities and nonspecific adsorption behavior that can be achieved using aptamer functionalization compared to antibody probes. 27,34 Tau 381 is one of six known variants ranging from 352 to 441 amino acids in length. 35 The relative abundance and molecular mechanism of each variant is still poorly understood and commercially available ELISA kits do not differentiate between variants, suggesting common epitope sites for antibody pairs across all species.…”
Section: Spr Detection Of Tau Proteinmentioning
confidence: 99%
“…Kads = 2.0 (±0.2) × 10 8 M -1 for IgE protein-DNA aptamer 36 and Kads = 4.8 (±0.1) × 10 8 M -1 for AAT protein-DNA aptamer affinity interactions. 27 The utilization of mixed MUA:MUD monolayers was then explored. The motivation for this is based on recent reports that this approach promotes reduced non-specific adsorption of proteins, 37 plus DNA, peptide 33 which is important for successful measurements in biofluids.…”
Section: Spr Detection Of Tau Proteinmentioning
confidence: 99%
“…In particular, AAT is an Alzheimer's disease biomarker with its affinity for the antiAAT used here recently described elsewhere. 42 This pairing was selected as a model system for proof-of-principle with antiBNP a non-specic control. As well as being a proven route for surface bioconjugation, this approach was also an attempt to achieve comparable surface charge, biomolecular coverage, and nonspecic interaction behaviors for each colloid sample and is the main reason that we used qNS's prepared using a variation of the CTAB chemistry used for the NR synthesis.…”
Section: Resultsmentioning
confidence: 99%